Validation of the Pulmonary Embolism Severity Index for risk stratification after acute pulmonary embolism in a cohort of patients in Brazil - Soriano,Leonardo de Araujo (2019)
ABSTRACT Objective: To validate the Pulmonary Embolism Severity Index (PESI), which was developed for risk stratification after acute pulmonary embolism (PE), for use in Brazil. Methods: This was a single-center retrospective study involving patients admitted to the emergency department with acute PE. The original and simplified versions of the PESI were calculated using hospital admission data from medical records. The outcome measure was the overall 30-day mortality rate. Results: We included 123 patients. The mean age was 57 ± 17 years, and there was a predominance of females, who accounted for 60% of the cohort. There were 28 deaths, translating to an overall 30-day mortality rate of 23%. In the cluster analysis by risk class, overall 30-day mortality was 2.40% for classes I-II, compared with 20.00% for classes III-IV-V (relative risk [RR] = 5.9; 95% CI: 1.88-18.51; p = 0.0002). When we calculated overall 30-day mortality using the simplified version (0 points vs. ≥ 1 point), we found it to be 3.25% for 0 points and 19.51% for ≥ 1 point (RR = 2.38; 95% CI: 0.89-6.38; p = 0.06). Using the original version, a survival analysis showed that risk classes I and II presented similar Kaplan-Meier curves (p = 0.59), as did risk classes III, IV, and V (p = 0.25). However, the curve of the clusters based on the original version, showed significantly higher mortality in the III-IV-V classes than in the I-II classes (RR = 7.63; 95% CI: 2.29-25.21; p = 0.0001). The cluster analysis based on the original version showed a greater area under the ROC curve than did the analysis based on the simplified version (0.70; 95% CI: 0.62-0.77 vs. 0.60; 95% CI: 0.51-0.67; p = 0.05). Conclusions: The PESI adequately predicted the prognosis after acute PE in this sample of the population of Brazil. The cluster analysis based on the original version is the most appropriate analysis in this setting.